The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/cam4.3578
|View full text |Cite
|
Sign up to set email alerts
|

Functional and genomic characterization of patient‐derived xenograft model to study the adaptation to mTORC1 inhibitor in clear cell renal cell carcinoma

Abstract: Resistance to the mechanistic target of rapamycin (mTOR) inhibitors, which are a standard treatment for advanced clear cell renal cell carcinoma (ccRCC), eventually develops in most cases. In this study, we established a patient‐derived xenograft (PDX) model which acquired resistance to the mTOR inhibitor temsirolimus, and explored the underlying mechanisms of resistance acquisition. Temsirolimus was administered to PDX model mice, and one cohort of PDX models acquired resistance after repeated passages. PDX t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…We established PDX and PDX-BF for patients with clear cell carcinoma. Studies have also been published on PDX from clear cell carcinoma in cervical cancer and renal cancer [45,46]. According to Serebrenik et al, PDX from ovarian clear cell carcinoma had histologically similar characteristics to primary tumors [47].…”
Section: Discussionmentioning
confidence: 99%
“…We established PDX and PDX-BF for patients with clear cell carcinoma. Studies have also been published on PDX from clear cell carcinoma in cervical cancer and renal cancer [45,46]. According to Serebrenik et al, PDX from ovarian clear cell carcinoma had histologically similar characteristics to primary tumors [47].…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicated that targeting the activity of ZDHHC2 could further inhibit the AKT signaling axis, thereby improving the sensitivity of ccRCC to TKIs and mTOR inhibitors. Moreover, a variety of factors confer resistance to mTOR inhibitors in renal cancer, such as HIF-mediated suppression of DEPTOR ( 62 ), aberrant expression of PTEN ( 63 ), and decreased DNMT1 enzyme activity ( 64 ). After long-term use of mTOR inhibitors leads to drug resistance, targeting ZDHHC2 can be used as a complementary and alternative therapy in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…To date, reports on OC have mainly focused on high-grade serous carcinoma. Studies have also been published on PDX from clear cell carcinoma in cervical cancer and renal cancer (33,34).…”
Section: Discussionmentioning
confidence: 99%